Pengaruh Profitabilitas, Likuiditas, Leverage Keuangan, Ukuran Perusahaan dan Kepemilikan Publik Terhadap Ketepatan Waktu Pelaporan Keuangan Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009 – 2011 - Valeda Rohana Utari; Muhammad Nuryatno Amin (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2011)
This research aims is to analyze the influence of profitability, liquidity, financialleverage, firm’s size, and shareholder’s dispersion on the timeliness of thefinancial statements. Sample of this research are 112 manufactures companiesthat consistent listed in Indonesia Stock Exchange (IDX) from period 2009 –2011 and selected by using purposive sampling method.Method used in analyzing data is logistic regression analysis. Result of thisresearch showed that profitability, liquidity, firm’s size, and shareholder’sdispersion have no effect on the timeliness of financial statement. Meanwhilefinancial leverage have an effect on the timeliness of financial statement.Keywords: Profitability, Liquidity, Financial Leverage, Firm’s Size, Shareholder’sDispersion, and The Timeliness of Financial Statement.